STRANDED Fm WHALl, BALAENOPTERA PHYSALUS(UNl^.) OFF MAGDALLA (SURAT) - Karbhari, J P (Indian Journal of Fisheries, 2011)
The morphometric measurements and the colour pattern of the body parts of the described whale closely ag^ed with the diagnostic chuacters of Bataenoptera pkysalus (linn.) described by Norman and Fraser (1937). The present record is the second instance of a stranded whale near Surat; (Gujarat).